A Practical Guide to Culturing Mouse and Human Bone Marrow Stromal Cells. (2nd May 2018) - Nemeth, K.; Mayer, B.; Sworder, B.J.; Kuznetsov, S.A.; Mezey, E.
Abstract: Bone marrow stromal cells (BMSCs, frequently also called MSCs) represent a cell population within the bone marrow, a subset of which contains multipotent stem cells. Their primary role is to produce and maintain both bone tissue and bone marrow microenvironment necessary for hematopoiesis. The latter is achieved by secreting a wide variety of different cytokines and growth factors, many of which also have a regulatory role in immune processes. BMSCs have recently been introduced into the field of immunobiology after their successful clinical use in GVHD was reported in 2004. Since then, numerous studies confirmed and expanded the knowledge on the immunosuppressive potential of BMSCs in various in vitro and in vivo models. Although the immunomodulatory capacity of BMSCs is well established, there are still many unanswered questions regarding the cytokines, chemokines, receptors, and molecular pathways that play a role in this effect. To study these cells and answer many of the questions, researchers must be able to reliably and reproducibly isolate, culture, and use these cells. Below a practical guide on how to culture and characterize mouse and human BMSCs, which can then be applied in various in vitro and in vivo assays, is provided. Curr. Protoc. Immunol . 102:22F.12.1‐22F.12.13. © 2013 by John Wiley & Sons, Inc.